Observation of quantum creep in oxygen deficient YBa2Cu3O7−δ at fields up to 7 T - van Dalen, A.J.J.; Griessen, R.; Libbrecht, S.; Osquiguil, E.; Bruynseraede, Y. (Elsevier, 1994)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina